“A Thousand of Kaleidoscopic Possibilities.” Postmemorial Agency in Jonathan Safran Foer’s Tree of Codes - Balestrino, Alice (Status Quaestionis, 2020)
This article focuses on Jonathan Safran Foer’s book-sculpture Tree of Codes (2010) as a postmemorial work formally intertextual and substantially metaliterary. In particular, it investigates the conundrum of the author’s and the reader’s generative agency within a postmemorial framework by dwelling on the highly experimental format of the book. Tree of Codes is the result of Foer’s performative approach to Bruno Schulz’s The Street of Crocodiles, from which the author carved out words, sentences and even whole pages in order to let a new text surface. The cut off pieces left material voids in the pages, empty rectangles displaying the intrinsic “extra-vacancy” of postmemorial narratives and producing a sense of bewilderment in the reader. As a consequence, readers seem to be invited to complement the author’s generative act with their interpretive potential, in “a thousand of kaleidoscopic possibilities” to inhabit the empty spaces, the vacancies of the postmemorial endeavor.